Kajian Fenomenologi: Kekerasan sebagai Perilaku Komunikasi terhadap Buruh Migran Perempuan Indonesia - Anggraeni Primawati; Ellys Lestari Pambayun (Jurnal Penelitian Kesejahteraan Sosial, 2013)
The research on violence as women migrant workers communication behavior in Jakarta was based on the observation of the reality of the violennce that endlessly (even flourishing) experienced by Indonesian women migrant workers in Jakarta. Physical, verbal, psychological, and even economic violence often experienced by women migrant workers. From the observations the problem then was found that violence, as inappropriate behavior experienced by women migrant workers, was closely related to the communication ability, language skill, and cultural understanding of women migrant workers at their work sites, Saudi Arabia and Malaysia. The theoretical basis used to analyze the research finding was phenomenological approach that especially explore the experience of actors or subjects (Indonesian women migrant workers) on the violence as inappropriate communication behavior, tends hiding, to be a fact that can be revealed. In addition, the perspective of intercultural communication included in this study, also used to see the context of communications and actions of women migrant workers in countries of different cultures, values, and ideologies, particularly stereotypes and prejudices involved in the violence on women migrant workers. Similarly, muted-group theory associated with this study, was used also to look at gender relations that occur among violent offenders, namely employers and migrant women (as victims of violence or inappropriate behavior) so they became a silent human being or powerless against the cultural and ideological domination of their employers.The research method used was a qualitative approach, exploring through phenomenological method that required in-depth investigation of the violence. The conclusion of the research was that the reality of violence behavior, as an inappropriate communication to Indonesian women migrant workers, was more physical, verbal, psychological, and economic expression in their private areas by the employers who still held the value, culture and patriarchal ideology, feudalism, and their lack understanding on the real Indonesian character and culture.